2013
DOI: 10.1257/aer.103.4.1212
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Effects of Personal and Corporate Income Tax Changes in the United States

Abstract: This paper estimates the dynamic effects of changes in taxes in the United States. We distinguish between changes in personal and corporate income taxes and develop a new narrative account of federal tax liability changes in these two tax components. We develop an estimator which uses narratively identified tax changes as proxies for structural tax shocks and apply it to quarterly post-WWII data. We find that short run output effects of tax shocks are large and that it is important to distinguish between diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
997
7
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 879 publications
(1,034 citation statements)
references
References 40 publications
26
997
7
4
Order By: Relevance
“…Using panel analysis, they find that a higher corporate income tax rate is related to slower economic growth or that a 1% cut in the corporate tax rate is associated with a 0.1-0.2% increase in the yearly growth rate. Mertens and Ravn (2013) find that 1% cut in the average personal income tax rate leads to increase real gross domestic product per capita by 1.4% in the first quarter and by up to 1.8% after three-quarter. Also, the same decrease of average corporate income tax rate raises real gross domestic product per capita by 0.4% in the first quarter and by 0.6% after one year.…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…Using panel analysis, they find that a higher corporate income tax rate is related to slower economic growth or that a 1% cut in the corporate tax rate is associated with a 0.1-0.2% increase in the yearly growth rate. Mertens and Ravn (2013) find that 1% cut in the average personal income tax rate leads to increase real gross domestic product per capita by 1.4% in the first quarter and by up to 1.8% after three-quarter. Also, the same decrease of average corporate income tax rate raises real gross domestic product per capita by 0.4% in the first quarter and by 0.6% after one year.…”
Section: Literature Reviewmentioning
confidence: 89%
“…There are many studies that have examined the effect of taxes on economic growth (Helms, 1985;Myles, 2000;Folster and Henrekson, 2001;Lee and Gordon, 2005;Tosun and Abizadeh, 2005;Bania et al 2007;Furceri and Karras, 2007;Reed, 2008;Romer and Romer, 2010;Gemmel et al 2011;Arnold et al 2011;Barro and Redlick, 2011;Ferede and Dahlby, 2012;Mertens and Ravn, 2013;Saqib et al 2014;Gale et al 2015;Ojong et al 2016). Engen and Skinner (1996) found that 2.5% point increase in tax to GDP ratio decreases GDP growth by 0.2-0.3%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To identify exogenous shocks to capital in ‡ows and their e¤ects on the other variables in the model, we employ the method of using external instruments in a structural VAR, as discussed in Stock and Watson (2012), Mertens andRavn (2013), andGertler andKaradi (2014). This is a two-step procedure.…”
Section: Identifying Exogenous Shocks To Capital In ‡Owsmentioning
confidence: 99%
“…We will instead rely on the method of using "external instruments in a structural VAR" as described in Stock and Watson (2012), Mertens andRavn (2013), andGertler andKaradi (2014). This is a two step proceedure where we will use external instruments, like the VIX, to identify the component of capital in ‡ows that are exogenous from the perspective of the receiving country, and use that as the exogenous shock from which to calculate impulse responses of various macroeconomic variables.…”
Section: Introductionmentioning
confidence: 99%
“…1 This proxy SVAR approach has proven to be very useful. Mertens and Ravn (2013) use it to merge the SVAR literature on tax shocks (Blanchard and Perotti, 2002;Mountford and Uhlig, 2009) with the narrative approach of Romer and Romer (2010), Gertler and Karadi (2015) and Lunsford (2016) use it to study the effects monetary policy shocks, Carriero et al (2015) use it to study the effects of uncertainty shocks, and Stock and Watson (2012) use it to study the effects of a large number of economic shocks, including oil shocks, productivity shocks, uncertainty shocks, and financial shocks. In addition, Mumtaz, Pinter, and Theodoridis (2015) show that it matches the effects of credit supply shocks from a dynamic stochastic general equilibrium model better than a Cholesky decomposition, and Drautzburg (2015) uses it to estimate a Bayesian VAR and a dynamic stochastic general equilibrium model.…”
Section: Introductionmentioning
confidence: 99%